Study of Tribological Properties of Multilayer Ti/TiN Coating Containing Stress Absorbing Layers - Kashyap A.; Harsha A.P.; Barshilia H.C.; Bonu V.; Kumar V. P.; Singh R.K. (My University, 2025)
Titanium (Ti)/titanium nitride (TiN) ultrathin multilayer coating was deposited on 100Cr6 substrates to investigate the friction and wear behavior in the presence of paraffin oil as a lubricant. The coating architecture was designed by adding thick stress absorbing layers (SAL a320 nm) in between the ultrathin Ti/TiN (3.5/4 nm) multilayer structure. The SAL reduces the residual stress in the coating. The coating had a NaCl type of structure, and X-ray diffraction (XRD) results showed the preferential crystallographic orientation of TiN along [111] direction. The tribological properties of the nanostructured coating were evaluated under reciprocating sliding conditions at varying loads (2 and 7 N), and temperature (30 and 100 °C) against 100Cr6 steel balls using paraffin oil as a lubricant. There was no considerable change in the coefficient of friction (COF) at different testing parameters. However, there was a significant drop in wear volume at high-Temperature testing conditions. The worn tracks were analyzed for their morphology and elemental composition through scanning electron microscope (SEM), energy dispersive X-ray analysis (EDAX), and Raman spectroscopy. © 2021 American Society of Mechanical Engineers (ASME). All rights reserved.